N6-methylated adenine on the target sites of mamA from Mycobacterium bovis BCG enhances macrophage activation by CpG DNA in mice - Tsukamoto, Yumiko; Tamura, Toshiki; Maeda, Yumi; Miyake, Kensuke; Ato, Manabu (Tuberculosis (Edinburgh, Scotland), 2020)
CpG motifs in DNA sequences are recognized by Toll-like receptor 9 and activate immune cells. Bacterial genomic DNA (gDNA) has modified cytosine bases (5-methylcytosine [5 mC]) and modified adenine bases (6-methyladenine [6 mA]). 5 mC inhibits immune activation by CpG DNA; however, it is unclear whether 6 mA inhibits immune activation by CpG DNA. Mycobacterium bovis BCG (BCG) has three adenine methyltransferases (MTases) that act on specific target sequences. In this study, we examined whether the 6 mA at the target sites of adenine MTases affected the immunostimulatory activity of CpG DNA. Our results showed that only 6 mA located at the target sequence of mamA, an adenine MTase from BCG, enhanced interleukin (IL)-12p40 production from murine bone marrow-derived macrophages (BMDMs) stimulated with CpG DNA. Enhancement of IL-12p40 production in BMDMs was also observed when BMDMs were stimulated with CpG DNA ligated to oligodeoxynucleotides (ODNs) harboring 6 mA. Accordingly, we then evaluated whether gDNA from adenine MTase-deficient BCG was less efficient with regard to stimulation of BMDMs. Indeed, gDNA from a mamA-deficient BCG had less ability to activate BMDMs than that from wild-type BCG. We concluded from these results that adenine methylation on ODNs and bacterial gDNA may enhance immune activity induced by CpG DNA. [Display omitted]